A retrofit circuit to increase output power of PV system during partial shading condition - Ramli, Mohd zulkifli; Salam, Zainal (2011)
In a typical photovoltaic (PV) distributed generation system, when part of the PV module is shaded, the bypass diode (that is connected in parallel to it) is used to protect the module from hot-spot damages. However, by employing this diode, the output power is reduced significantly because the power generated from the shaded module is totally unusable. Furthermore, when the current flows through the bypass diode, conduction losses occur which further degrade the system efficiency. In this paper, a simple retrofit circuit is proposed to increase the output power of PV system under partial shading condition. The idea is to utilize the current generated by the shaded module, detour it to a power electronics circuit and then process it to become part of the output power. Consequently, the inclusion of the retrofit circuit enables to system to deliver more power compared to the bypass diode method. Simulation results show marked improvement in the efficiency, especially under heavy partial shading condition.